Biomimicry of Palm Tree Leaves Form and Pattern on Building Form - Agus Salim, N.A.; Mydin, M.A.O; Md. Ulang, N. H. (EDP Sciences, 2014)
This article is a study on biomimicry of palm tree towards a building form. It is to find a suitable form and pattern that can be applied to building shell to ease building maintenance operation beside to enhance the aesthetic value of a building architecture. The research has been carried out by observation and modeling on some various species of palm tree’s patterns and forms. The result expectation can be found at the end of this research by producing the best pattern of palm tree that can be adapted to building envelop as the whole form of a building.